2017
DOI: 10.1681/asn.2016050519
|View full text |Cite
|
Sign up to set email alerts
|

Targeting mTOR Signaling Can Prevent the Progression of FSGS

Abstract: Mammalian target of rapamycin (mTOR) signaling is involved in a variety of kidney diseases. Clinical trials administering mTOR inhibitors to patients with FSGS, a prototypic podocyte disease, led to conflicting results, ranging from remission to deterioration of kidney function. Here, we combined complex genetic titration of mTOR complex 1 (mTORC1) levels in murine glomerular disease models, pharmacologic studies, and human studies to precisely delineate the role of mTOR in FSGS. mTORC1 target genes were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 51 publications
5
67
1
Order By: Relevance
“…Establishing a valid relationship between mitochondrial dysfunction and CKD progression, however, has been elusive since this interaction seems to vary depending the definition of mitochondrial dysfunction, specific conditions, and the population studied or the model examined. Despite all these differences, there are some hallmark features of mitochondrial dysfunction that are commonly described in the context of CKD which include, changes in mitochondrial morphology and mitochondrial remodeling, enhanced mitochondrial oxidative stress, and a significant decrease in mitochondrial biogenesis and in ATP production (2). …”
Section: Introductionmentioning
confidence: 99%
“…Establishing a valid relationship between mitochondrial dysfunction and CKD progression, however, has been elusive since this interaction seems to vary depending the definition of mitochondrial dysfunction, specific conditions, and the population studied or the model examined. Despite all these differences, there are some hallmark features of mitochondrial dysfunction that are commonly described in the context of CKD which include, changes in mitochondrial morphology and mitochondrial remodeling, enhanced mitochondrial oxidative stress, and a significant decrease in mitochondrial biogenesis and in ATP production (2). …”
Section: Introductionmentioning
confidence: 99%
“…15 Positive effects attributed to RAPA inhibition of mTORC include reduced body weight and adiposity, 68 protection against development of diabetic nephropathy, 9,10 and improvement in hepatic function 1114 However, RAPA inhibition of mTORC can lead to exacerbated hyperglycemia, glucose intolerance, and hyperlipidemia in both murine models 8,15,16 and renal transplant and cancer patients treated with immunosuppressive rapamycin analogs. 17,18 Although we have not examined RAPA inhibition of mTORC1 or mTORC2 in our studies, it has been suggested by others that negative RAPA-mediated effects on pancreatic islets and glucose homeostasis occur via inhibition of the mTORC2 complex, whereas positive benefits that promote longevity derive from RAPA inhibition of the mTORC1 complex.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that inhibition of the mTORC (mechanistic target of rapamycin complex) pathway by rapamycin (RAPA) can lead to increased longevity in mice as well as other organisms, such as yeast, Drosophila, and Caenorhabditis elegans. [1][2][3][4][5] Positive effects attributed to RAPA inhibition of mTORC include reduced body weight and adiposity, [6][7][8] protection against development of diabetic nephropathy, 9,10 and improvement in hepatic function. [11][12][13][14] However, RAPA inhibition of mTORC can lead to exacerbated hyperglycemia, glucose intolerance, and hyperlipidemia in both murine models 8,15,16 and renal transplant and cancer patients treated with immunosuppressive RAPA analogs.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have shown that mTOR signaling is involved in an assortment of renal diseases [12,13,[21][22][23], and abnormal mTOR integrated signals can be activated by numerous molecular reactions in podocytes. Such reactions include the mislocalization of slit diaphragm proteins and the induction of an epithelial-mesenchymal transition-like phenotypic switch with enhanced endoplasmic reticulum stress in podocytes [22].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that podocyte injury and loss are commonly followed by adaptive mammalian target-of-rapamycin (mTOR) activation [12], which can contribute to the progression of glomerular disease, e.g., crescentic glomerulonephritis [13], membranous nephropathy [14], and Adriamycin-induced podocyte apoptosis [15]. mTOR is a serine/threonine protein kinase in the PI3K-related kinase family that controls cellular growth, survival, and metabolism.…”
Section: Introductionmentioning
confidence: 99%